Identification of a novel missense eya4 mutation causing autosomal dominant non"‘syndromic hearing loss in a chinese family - Xiao, Shu-ying; Qu, Jing; Zhang, Qin; Ao, Ting; Zhang, Jun; Zhang, Rui-hua (Cellular and Molecular Biology, 2019)
The aim of this study was to identify the novel missense eya4 mutation which cause autosomal dominant non syndromic hearing loss In a Chinese family. Hearing loss is the most common sensory deficit in humans, but the middle-frequency sensorineural hearing loss (MFSNHL) is rare among hereditary non-syndromic hearing loss, and EYA4 is one of the genes reported to be associated with MFSNHL. A genetic analysis of a Chinese family with autosomal dominant non"‘syndromic progressive hearing impairment was conducted and assessed. Targeted exome sequencing, conducted using DNA samples of an affected member in this family, revealed a novel heterozygous missense mutation c.1855T>G in exon 20 of EYA4, causing amino-acid (aa) substitution Gly for Trp at a conserved position aa-619. The p.W619G mutation related to hearing loss in this Chinese family was validated by Sanger sequencing. Bioinformatic analysis confirmed the pathogenic effects of this mutation. We identified the novel missense mutation c.1855T>G (p.W619G) in EYA4 causing autosomal dominant non-syndromic hearing impairment in the selected Chinese family.